2007
DOI: 10.1158/1078-0432.ccr-07-0507
|View full text |Cite
|
Sign up to set email alerts
|

Augmented HER-2–Specific Immunity during Treatment with Trastuzumab and Chemotherapy

Abstract: Purpose: Passive immunotherapy with antitumor antibodies has the potential to induce active tumor immunity via the opsonic enhancement of immunogenicity of tumor antigen. We have assessed whether immune sensitization to the HER-2/neu tumor antigen occurs during treatment with the anti-HER-2/neu monoclonal antibody trastuzumab. Experimental Design: Twenty-seven patients treated with trastuzumab and chemotherapy were assessed for the induction of HER-2/neu^specific immunity. Sera and peripheral blood mononuclear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
148
0
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(161 citation statements)
references
References 39 publications
8
148
0
5
Order By: Relevance
“…A more recent study indicated that anti-cancer mAb therapies can function to augment endogenous antibody responses to tumor surface antigens, in particular the antigen HER2. 88 Our in vitro studies have shown that the predominant form of cleaved IgG most likely present on the surface of the tumor cell would be the single-cleaved intermediate. 9 Due to the difficulty of identifying the single-cleaved intermediate under native conditions, the presence of the single heavy chain cleavage would most likely go undetected; however, we have identified the presence of single-cleaved IgGs in breast cancer tumor extracts.…”
Section: Discussionmentioning
confidence: 89%
“…A more recent study indicated that anti-cancer mAb therapies can function to augment endogenous antibody responses to tumor surface antigens, in particular the antigen HER2. 88 Our in vitro studies have shown that the predominant form of cleaved IgG most likely present on the surface of the tumor cell would be the single-cleaved intermediate. 9 Due to the difficulty of identifying the single-cleaved intermediate under native conditions, the presence of the single heavy chain cleavage would most likely go undetected; however, we have identified the presence of single-cleaved IgGs in breast cancer tumor extracts.…”
Section: Discussionmentioning
confidence: 89%
“…Although CIR-PBL showed higher rate of tumor inhibition than Herceptin in our study, more aggressive treatment with Herceptin including frequent infusion and the use of higher dose can result in better clinical outcome than infusion of CIR-PBL, as used by other groups. [23][24][25][26] Several reports have contributed to elucidate mechanism of Herceptin including interference receptor dimerization, blockade of phosphorylation of ErbB2 and ErbB3, inhibition of mitogen-activated protein kinase activity, and suppression of phosphatidylinositol 3 0 -kinase, and Akt. 38,39 In addition, it was proposed that Herceptin generates antibody-dependent cell-mediated cytotoxicity effect involving host NK cells.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21][22] Many methods have been used to therapeutically target Her-2-overexpressing cancers, including the use of anti-Her-2/neu antibodies. [23][24][25][26] Trastuzumab also known as Herceptin for humanized form, was found to inhibit the proliferation of human cancer cells that overexpress Her-2/neu, both in vitro and in vivo. 27,28 However, the clinical benefit is limited because its resistance to Herceptin therapy among Her-2/neu-overexpressing cancer cells arises in less than 12 months.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Trastuzumab treatment can induce antitumor cytotoxic T lymphocytes (CTLs) in patients. 21 Similarly, it was demonstrated that a mouse anti-epidermal growth factor receptor antibody could control metastasis in a CD4 and CD8 T cell-dependent manner. 22 However, the mechanisms by which antibody therapy generates activate adaptive immunity has remained largely unclear.…”
Section: Antibody Therapymentioning
confidence: 96%